2016
DOI: 10.1073/pnas.1610544113
|View full text |Cite
|
Sign up to set email alerts
|

Tethered IL-15 augments antitumor activity and promotes a stem-cell memory subset in tumor-specific T cells

Abstract: Adoptive immunotherapy retargeting T cells to CD19 via a chimeric antigen receptor (CAR) is an investigational treatment capable of inducing complete tumor regression of B-cell malignancies when there is sustained survival of infused cells. T-memory stem cells (TSCM) retain superior potential for long-lived persistence, but challenges exist in manufacturing this T-cell subset because they are rare among circulating lymphocytes. We report a clinically relevant approach to generating CAR+T cells with preserved T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
290
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 362 publications
(296 citation statements)
references
References 71 publications
3
290
3
Order By: Relevance
“…The SB system can also be adapted to express more than one transposon. In a technology dubbed 'double transposition', three DNA plasmids (two transposons and one transposase) have been electrotransferred into T cells to co-express CAR and mbIL15 [114]. The signaling through the second-generation CAR and the common g-chain cytokine receptor results in a T cell that combines 'signal 1 and 2' with 'signal 3' [114].…”
Section: Transfectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SB system can also be adapted to express more than one transposon. In a technology dubbed 'double transposition', three DNA plasmids (two transposons and one transposase) have been electrotransferred into T cells to co-express CAR and mbIL15 [114]. The signaling through the second-generation CAR and the common g-chain cytokine receptor results in a T cell that combines 'signal 1 and 2' with 'signal 3' [114].…”
Section: Transfectionmentioning
confidence: 99%
“…In a technology dubbed 'double transposition', three DNA plasmids (two transposons and one transposase) have been electrotransferred into T cells to co-express CAR and mbIL15 [114]. The signaling through the second-generation CAR and the common g-chain cytokine receptor results in a T cell that combines 'signal 1 and 2' with 'signal 3' [114]. This results in fully competent activation and the preservation of the key stem cell memory T cell (T SCM ) subpopulation that is correlated with antitumor effects [115].…”
Section: Transfectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The signaling through the second-generation CAR and the common g-chain cytokine receptor results in a T cell that combines "signal 1 and 2" with "signal 3", resulting in fully-competent activation, preservation of key stem-cell memory T-cell (T SCM ) sub-populations, and superior persistence and killing of CD19 + tumor in mice compared with current CAR + T cells. 28,29 The long-lived T cells were CD45RO neg CCR7 + CD95 + , phenotypically most similar to T SCM , and furthermore possessed a memory-like transcriptional profile. The PD-1/PD-L1 axis may impact CAR T cells similarly to nontransferred T cells.…”
Section: Current Challengesmentioning
confidence: 99%
“…Preclinical trials in MCL have also shown improved CAR-T responses and reduced CRS when combined with ibrutinib (Bruton's tyrosine kinase inhibitor) and in CLL when ibrutinib is given prior to CAR-T cell infusion [73,74]. Other preclinical trials have developed CAR-T cells that co-express cytokines (IL-12, IL-15, IL-18 or interferon 1β) when the cells engage with a target cancer cell, to possibly enhance the CD19-directed anti-tumor effect [75][76][77][78][79]. However, a clinical trial of IL-12 coexpressing CAR-T cells in melanoma patients was recently discontinued due to severe IL-12 toxicity [80].…”
Section: Car-t Cell Combination Therapiesmentioning
confidence: 99%